2010
DOI: 10.1007/s11172-010-0177-1
|View full text |Cite
|
Sign up to set email alerts
|

3-(4-Thiocarbamoyl-1,2,3-triazol-1-yl)benzo-15-crown-5: synthesis and properties

Abstract: A reaction of 1,2,3 thiadiazole 4 carbaldehyde with 3 aminobenzo 15 crown 5 involves the Cornforth rearrangement of the 1,2,3 thiadiazole ring, which leads to 1,2,3 triazole 4 carbothioamide containing the benzocrown ether substituent in position 1 of the triazole ring. Reversible formation of the isomeric thiadiazole occurs in aprotic nonpolar solvents such as deuterated chloroform. These compounds are suitable for extraction of α amino acids from an aqueous phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Thus thiadiazoles 48 undergo Dimroth-type rearrangement to form 1H-1,2,3-triazol-3-ium-5-thiolates 49, in good yields[34]. 4-Carbimino-1,2,3-thiadiazoles 48 (R 3 = HC = NR) formed by reaction of 4-formyl-1,2,3-thiadiazole with amines, are labile and rearrange to 1,2,3-triazol-4-carbothioamides 50 under the conditions used for their generation[39,40]. It was found that interaction of 1,2,3-thiadiazolylhydrazones of acetophenones with phosphorus pentachloride in benzene or toluene leads to 5H-[1,2,3]triazolo[5,1-b][1,3,4] thiadiazines 51.…”
mentioning
confidence: 99%
“…Thus thiadiazoles 48 undergo Dimroth-type rearrangement to form 1H-1,2,3-triazol-3-ium-5-thiolates 49, in good yields[34]. 4-Carbimino-1,2,3-thiadiazoles 48 (R 3 = HC = NR) formed by reaction of 4-formyl-1,2,3-thiadiazole with amines, are labile and rearrange to 1,2,3-triazol-4-carbothioamides 50 under the conditions used for their generation[39,40]. It was found that interaction of 1,2,3-thiadiazolylhydrazones of acetophenones with phosphorus pentachloride in benzene or toluene leads to 5H-[1,2,3]triazolo[5,1-b][1,3,4] thiadiazines 51.…”
mentioning
confidence: 99%